Annotating Throughout or Annotating Afterward: Preservice Teachers’ Experiences with the ANNOTO Hyper-Video in Blended Learning - Liat Biberman-Shalev (Education Sciences, 2024)
This study aims to explore the perspectives of pre-service teachers (PSTs) regarding their experiences with the ANNOTO personal note feature within a blended learning (BL) context. Employing qualitative research methods, the analysis incorporates reflections from 45 PSTs, insights derived from two focus groups, and data gathered through semi-structured interviews. The objective is to comprehend how PSTs engaged with ANNOTO’s personal note during their learning experiences and how they perceived its role in shaping their professional development. The findings underscore a predominantly positive experience among PSTs, with their perceptions linked to heightened motivation and meaningful learning. Additionally, the study identified three distinct annotating styles—annotating throughout watching, annotating after watching, and a combination of both—each associated with enhanced concentration, memory prompting, and improved writing skills. Furthermore, PSTs articulated professional insights related to teacher and student agency, encompassing themes such as the use of video as a teaching tool, active learning, self-directed learning, scaffolding, critical thinking, and temporal considerations aligned with students’ needs. The principal implications center on the necessity of engaging in discussions with PSTs regarding the integration of hyper-video and the pedagogical approaches it may endorse.